Efeito da terapia fotodinâmica na halitose: revisão sistemática de ensaios clínicos controlados randomizados - Motta, Pamella de Barros (2021)
Halitosis is a term that defines any odor or foul-smelling from the oral cavity, which may be local or systemic in origin. The conventional treatments used to control halitosis basically consist in the use of toothpastes and rinses containing bactericidal substances and the use of a tongue scraper. APDT is a treatment in which a photosensitizing agent is used, in the presence of light, produces free oxygen radicals leading to cell death, in the case of halitosis, which has the main etiological factor related to the presence of anaerobic bacteria. Therefore, the present study aimed to conduct a systematic review of randomized controlled clinical trials that present aPDT protocols for the treatment of halitosis to assess their effectiveness. For the systematic review, scientific articles published between 2010 and 2020 were selected. Searches were carried out in the following databases: PubMed, Web of Science, Google Scholar and MEDLINE. The search terms used were “halitosis”, “photochemotherapy”, “lasers” AND “halitosis”, “light” AND “halitosis”. After the systematic review it is possible to conclude that the antimicrobial photodynamic therapy applied alone characterizes an effective treatment in the control of halitosis